The effect of intrathecal bupivacaine/morphine on quality of recovery in robot‐assisted radical prostatectomy: a randomised controlled trial - Koning, M. V. (John Wiley and Sons Inc., 2019)

(untitled) (Anaesthesia)
Robot‐assisted radical prostatectomy causes discomfort in the immediate postoperative period. This randomised controlled trial investigated if intrathecal bupivacaine/morphine, in addition to general anaesthesia, could be beneficial for the postoperative quality of recovery. One hundred and fifty‐five patients were randomly allocated to an intervention group that received intrathecal 12.5 mg bupivacaine/300 μg morphine (20% dose reduction in patients > 75 years) or a control group receiving a subcutaneous sham injection and an intravenous loading dose of 0.1 mg.kg(−1) morphine. Both groups received standardised general anaesthesia and the same postoperative analgesic regimen. The primary outcome was a decrease in the Quality of Recovery‐15 (QoR‐15) questionnaire score on postoperative day 1. The intervention group (n = 76) had less reduction in QoR‐15 on postoperative day 1; median (IQR [range]) 10% (1–8 [−60% to 50%]) vs. 13% (5–24 [−6% to 50%]), p = 0.019, and used less morphine during the admission; 2 mg (1–7 [0–41 mg]) vs. 15 mg (12–20 [8–61 mg]), p < 0.001. Furthermore, they perceived lower pain scores during exertion; numeric rating scale (NRS) 3 (1–6 [0–9]) vs. 5 (3–7 [0–9]), p = 0.001; less bladder spasms (NRS 1 (0–2 [0–10]) vs. 2 (0–5 [0–10]), p = 0.001 and less sedation; NRS 2 (0–3 [0–10]) vs. 3 (2–6 [0–10]), p = 0.005. Moreover, the intervention group used less rescue medication. Pruritus was more severe in the intervention group; NRS 4 (1–7 [0–10]) vs. 0 (0–1 [0–10]), p = 0.000. We conclude that despite a modest increase in the incidence of pruritus, multimodal pain management with intrathecal bupivacaine/morphine remains a viable option for robot‐assisted radical prostatectomy.